Beneficial effects of working later in life on the health of community‐dwelling older adults. Issue 2 (2nd November 2017) - Tomioka, Kimiko; Kurumatani, Norio; Hosoi, Hiroshi
Abstract : Aim: Evidence regarding the health effects of working lack coherence. This study seeks to determine if continuing to work into older age benefits or damages one's health. Methods: Baseline questionnaires were mailed to 15 058 individuals aged ≥65 years living in two municipalities in Nara Prefecture, Japan. Of these, 11 183 were returned. Analyses were limited to those who maintained each health index at baseline. We followed the participants for 3 years, and examined three health outcomes: long‐term care need, cognitive decline and instrumental activities of daily living (IADL) decline. Participants were divided into four groups according to their baseline working status and follow‐up status: non‐working, retired, initiating work and continuing to work. Results: After covariate adjustments, older men who initiated work had a decreased likelihood for long‐term care (odds ratio [OR] 0.41, 95% confidence interval [CI] 0.17–0.98) and IADL decline (OR 0.44, 95% CI 0.23–0.84), older men who continued working prevented the onset of long‐term care (OR 0.22, 95% CI 0.09–0.54) and cognitive decline (OR 0.69, 95% CI 0.50–0.96), older women who initiated working were less likely to require long‐term care (OR 0.24, 95% CI 0.09–0.66) and IADL decline (OR 0.38, 95% CI 0.16–0.88), and older women who continued working had a significantly lower risk of IADL decline (OR 0.39, 95% CI 0.16–0.99), compared with the non‐working group. Retirees did not differ from the non‐working group in any of the health outcomes. Conclusions: Although beneficial effects vary by sex and type of health outcomes, the present findings suggest that policies encouraging older people to participate in the workforce contribute to extending healthy life expectancy.Geriatr Gerontol Int 2018; 18: 308–314 .